2020
DOI: 10.21071/az.v69i265.5040
|View full text |Cite
|
Sign up to set email alerts
|

Tambaqui de tanque-rede: qualidade microbiológica, valor nutricional e rendimento

Abstract: O tambaqui é consumido tradicionalmente em tamanho comercial (1 a 3 kg), mas também entre 0,350 a 0,450 kg, sendo denominado Curumim(C). Objetivou-se avaliar a qualidade microbiológica do tambaqui em tamanho comercial (TC) e caracterizar o valor nutricional e rendimento de tambaquis em duas classes de tamanho: Curumim (C) e TC, provenientes de tanques-rede. O efeito do tamanho sobre a composição centesimal e rendimento do peixe foi avaliado em delineamento inteiramente casualizado com 12 repetições, enquanto p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
1
2
0
1
Order By: Relevance
“…Therefore, in fish such as tambaqui fry, moisture makes up about 65% of the fillet (Terrazas et al, 2002;Mendonça et al, 2011), while in the juvenile phase (Lima et al, 2018;Oliveira et al, 2020) up to adult (Sales & Maia, 2013;Mesquita, 2013;Lima et al, 2018) values can vary from 70 to 80% of water present in the meat, corroborating with the results presented here since both wild tambaqui (≈ 79.8) and farmed tambaqui (≈ 76.5) had similar average moisture levels. Other species of fish such as pacu (Piaractus mesopotamicus Holmberg, 1887) (Ramos et al, 2008;Cortez et al, 2010;Zuanazzi et al, 2013), tilápia (Oreochromis niloticus Linnaeus, 1758) (Cortez et al, 2010;Sales & Maia, 2012;Colpini et al, 2017) and piauçu (Leporinus microcephalus Garavello & Britski, 1988) (Lanzarin et al, 2017) showed the same pattern with moisture ranging from 60 to 80%, both for wild fish and for farmed fish.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, in fish such as tambaqui fry, moisture makes up about 65% of the fillet (Terrazas et al, 2002;Mendonça et al, 2011), while in the juvenile phase (Lima et al, 2018;Oliveira et al, 2020) up to adult (Sales & Maia, 2013;Mesquita, 2013;Lima et al, 2018) values can vary from 70 to 80% of water present in the meat, corroborating with the results presented here since both wild tambaqui (≈ 79.8) and farmed tambaqui (≈ 76.5) had similar average moisture levels. Other species of fish such as pacu (Piaractus mesopotamicus Holmberg, 1887) (Ramos et al, 2008;Cortez et al, 2010;Zuanazzi et al, 2013), tilápia (Oreochromis niloticus Linnaeus, 1758) (Cortez et al, 2010;Sales & Maia, 2012;Colpini et al, 2017) and piauçu (Leporinus microcephalus Garavello & Britski, 1988) (Lanzarin et al, 2017) showed the same pattern with moisture ranging from 60 to 80%, both for wild fish and for farmed fish.…”
Section: Discussionsupporting
confidence: 87%
“…Tambaqui fry exhibit high ash content, varying between 10 and 15% (Terrazas et al, 2002;Mendonça et al, 2011). These values decrease as individuals grow, since juveniles have values between 0.7 and 2.9% (Lima et al, 2018;Oliveira et al, 2020), and the same pattern is observed in adulthood, from 0.7 to 2.7% (Sales & Maia, 2013;Mesquita, 2013;Lima et al, 2018). Also, adult piauçu (Lanzarin et al, 2017) and juvenile tilápia (Cortez et al, 2010;Sales & Maia, 2012;Colpini et al, 2017) and pacu (Ramos et al, 2008;Cortez et al, 2010;Zuanazzi et al, 2013), have these same characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De modo a garantir a segurança sanitária do cultivo, e evitar, por exemplo, a elevação da concentração de CT, E. coli e NH 3 no ambiente aquático que inviabilize o sistema de produção. Dos Santos Oliveira et al (2020) identificaram a presença de coliformes totais em 75% das amostras de Tambaqui curumim, e isso poderia indicar contaminação da água onde esses peixes foram criados.…”
Section: Discussionunclassified